CO2 laser-assisted sclerectomy surgery for secondary open-angle glaucoma after vitrectomy - Li, Zheng; Wang, Ao; Zhu, Mingqiong; Zhou, Na; Liu, Li; Li, Qiaolian; Kuang, Guoping (Frontiers in Medicine, 2024)
Purpose To explore the efficiency and safety of carbon dioxide (CO2) laser-assisted sclerectomy surgery (CLASS) in Chinese patients with glaucoma secondary to vitrectomy. Methods This retrospective study consisted of 16 eyes from 16 patients with glaucoma secondary to vitrectomy who underwent CLASS and were followed up for 12 months. Main outcome measures included preoperative and postoperative intraocular pressure, best corrected visual acuity (BCVA), number of anti-glaucoma medications, and postoperative surgical success rate and complications. Results The postoperative IOP and number of anti-glaucoma medications used at all follow-up time point were significantly lower than those preoperatively. The difference in BCVA was not significant before and after surgery. The main complicatios were peripheral anterior synechiae (PAS) and scleral reservoir reduction, which were controlled after neodymium-doped yttrium aluminum garnet (Nd:YAG) laser, 2 (12.50%) patients underwent re-operation. The complete and total success rates at 12 months were 68.75% and 87.50%, respectively. Conclusion CLASS is a safe and effective procedure for Chinese patients with glaucoma secondary to vitrectomy. PAS and scleral reservoir reduction is a major contributor to postoperative IOP elevation, and trabecular minimally invasive perforation with the Nd:YAG laser is effective in lowering IOP and increasing scleral cistern volume.